Interpretation of Zakat Perspectitive of the Hadith Ahkam Fii Al-Muamalah - Adawiah, Amalia Muazzah; Komaruddin, Koko; Sar’an, Muhamad (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2023)
Zakat is an obligation to all muslims who are capable or have reached an nisab in it’s possession. Zakat was essentially a vertical and horizontal relationship. In a horizontal relationship, zakat’s purpose is not just conserving the poor, but has a more permanent purpose of raising poverty, the purpose in this article to discuss the question of the zakat study, referring to the prophet’s hadiths, As for the approach in this article using a qualitative approach through library study (library research) which is the method for data collection by understanding and studying theories from various literature ranging from books and journals relating to the subject. The result of this article was that zakat was obligatory to religious believers who had a set minimum of property (nishab) and had a one-year period. In addition to consecrate property, zakat was viewed as an obligation to the owner of the treasure to impose the rights of others on the property obtained.